1- Biafra in the Present: Trauma of a Loss - Oloyede, Olajidee (African Sociological Review, 2009)
This paper forms part of a wider attempt at engaging the issues of nation building, war, and trauma within the context of a developing sociology of trauma. It focuses, specifically, on Biafra, a recurring issue in the political and economic discussions in Nigeria. It delimits the focus to trauma. The Igbo perception of their increased marginalisation in the scheme of things in contemporary Nigeria brings to the fore the idea of Biafra, an Igbo attempt to create an Igbo nation-state which subsequently resulted into the war which foreshadowed many of the conflicts that would threaten to ‘shatter’ many post colonial Africa. The war was traumatic: it inflicted fear and suffering. With the use of cultural trauma and the notion of the loss of assumptive world, the paper suggests that its loss was more traumatic because of the shattering of the cognitive representation of Biafra, an entity which was to bring a sense of belonging and connection that would cohere the Igbo being. In the wake of the loss of Biafra, the assumptive world of the Igbo was shattered. The paper suggests further that current recollection of Biafra by the Igbo serves as an illustration of the ‘collective trauma’ of its loss. The theoretical basis for the argument in this paper is that Biafra is rooted in the psyche of the Igbo.